1999
DOI: 10.1149/1.1391637
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fe‐Rich Intermetallic Inclusions on Pit Initiation on Aluminum Alloys in Aerated NaCl

Abstract: The role that Al3normalFe intermetallic inclusions play during initiation of pitting corrosion on aluminum alloys was investigated in 0.6 M NaCl. In aerated solutions microscopic observations showed the growth of cavities in the host metal adjacent to inclusions. The rest potential of synthetic Al3normalFe was measured in aerated and deaerated NaCl solutions over a range of bulk pH values between 2 and 12 and was found to act as a cathode. In aerated solutions rotating disk electrode experiments on synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(137 citation statements)
references
References 10 publications
4
131
1
1
Order By: Relevance
“…The agreement is good in the whole frequency range; the small difference appearing in the high frequency range is attributed to current and potentials distribution induced by geometry effect, which were not taking into account in the model. It has to be noted that the presence of Fe-rich intermetallic phases can also contribute to the nonuniformity of the surface [22][23][24][25], but their influence were considered to be negligible in comparison with that of the classical nonuniform current distribution on the disk electrode in the present work.…”
Section: Eis Modelmentioning
confidence: 95%
“…The agreement is good in the whole frequency range; the small difference appearing in the high frequency range is attributed to current and potentials distribution induced by geometry effect, which were not taking into account in the model. It has to be noted that the presence of Fe-rich intermetallic phases can also contribute to the nonuniformity of the surface [22][23][24][25], but their influence were considered to be negligible in comparison with that of the classical nonuniform current distribution on the disk electrode in the present work.…”
Section: Eis Modelmentioning
confidence: 95%
“…7), line X represents oxygen-water equilibrium, and line Y represents hydrogen-water equilibrium. [13][14][15]23,24 The other common cathodic reaction that occurs during metal corrosion is reduction of dissolved oxygen (Eq. 1.…”
Section: Resultsmentioning
confidence: 99%
“…The stable potential region for water is between lines X and Y and is expressed by Eq. [23][24][25][26] Because noble intermetallic particles are known to be better oxygen reduction electrocatalysts than oxide surfaces, 24,26 reaction (IV) would be expected to occur in the vicinity of IMCs À 0:242 À 0:0592pH nðvs:SCEÞ 0:986 À 0:0592pH Decreasing the potential of the electrode to a value less than that given by line Y causes the cathodic evolution of hydrogen gas at 1 atm hydrogen pressure from the electrolyte expressed by Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, lots of hydroxyl ions are produced causing localized alkalization of the solution near the cathodic particles. A pH value as high as 9.5 was measured around Al 3 Fe in AA6061 alloy [75]. Besides, various modeling studies have indicated that a localized pH (near cathodic particle) approaching 10 is possible for a neutral solution [76,77].…”
Section: Effects Of Particles Microchemistry On Pittingmentioning
confidence: 98%